Cover Feature: All‐in‐One: Electroactive Nanocarbon as Simultaneous Platform and Label for Single‐Step Biosensing (Chem. Eur. J. 24/2018). Issue 24 (24th March 2018) - Cheng, Zhao Xuan; Bonanni, Alessandra
Abstract : It is demonstrated that an electroactive nanocarbon material can simultaneously work as both platform and label for the detection of mycotoxins. The intensity of peak current reflects the availability of oxygen functionalities for reduction, which can be directly correlated to the specific biorecognition event. Upon immobilization of DNA aptamer and formation of the aptamer‐mycotoxin conjugate, the electroactivity of the material results altered, enabling precise quantification of the analyte under investigation and good selectivity. More information can be found in the Full Paper by A. Bonanni and Z. X. Cheng onpage 6380 .